Automation Watering System Berbasis IoT Cerdas pada Bawang Merah - Marwondo, Marwondo; Sardjono, Sardjono; Yonathan, Michael A. (INTERNAL (Information System Journal), 2023)
In the current era of rapid technological development, smart irrigation systems are increasingly needed in cultivating crops, including shallots. This system was built to increase plant productivity by using smart irrigation to anticipate climate changes that occur. Through the use of IoT technology and expert systems, this system can provide effective solutions in optimizing the growth and quality of shallots. This Automation Watering System uses a microcontroller as the brain of the system which is connected to various sensors and actuators. The microcontroller takes data from sensors and sends it to the server via a WiFi network or other wireless protocol. The server then analyzes the data using an expert system that has been programmed with expert knowledge in the field of shallot cultivation. This Automation Watering System is able to optimize water use. and avoid excess or lack of watering. The results showed that with the integration of the Internet of Things (IoT) and expert systems, this system can provide smart solutions in shallot cultivation, ensure optimal growth, and produce better harvest results.